SCALE INVARIANCES IN THE MORPHOLOGY AND EVOLUTION OF BRAIDED RIVERS - Foufoula-Georgiou E.; Sapozhnikov V. (My University, 2001)
This paper presents an overview and synthesis of an extensive research effort to characterize and quantify scale invariances in the morphology and evolution of braided rivers. Braided rivers were shown to exhibit anisotropic spatial scaling (self-affinity) in their morphology, implying a statistical scale invariance under appropriate rescaling of the axes along and perpendicular to the main direction of flow. The scaling exponents were found similar in rivers of diverse flow regimes, slopes, types of bed material and braid plain widths, indicating the presence of universal features in the underlying mechanisms responsible for the formation of their spatial structure. In regions where predominant geologic controls or predominant flow paths were present, no spatial scaling was found. Regarding their spatiotemporal evolution, braided rivers were found to exhibit dynamic scaling, implying that a smaller part of a braided river evolves identically to a larger one provided that space and time are appropriately normalized. Based on these findings, and some additional analysis of experimental rivers as they approach equilibrium, it was concluded that the mechanism bringing braided rivers to a state where they show spatial and temporal scaling is self-organized criticality and inferences about the physical mechanisms of self-organization were suggested.
Keywords: SELF-AFFINITY; DYNAMIC SCALING; SELF-ORGANIZED CRITICALITY